If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(p+6)-5(8p+1)=-35
We move all terms to the left:
-5(p+6)-5(8p+1)-(-35)=0
We add all the numbers together, and all the variables
-5(p+6)-5(8p+1)+35=0
We multiply parentheses
-5p-40p-30-5+35=0
We add all the numbers together, and all the variables
-45p=0
p=0/-45
p=0
| 30=-2x+10 | | 7x-2=17x | | 10=0.049x^2 | | |x+8|=21 | | 10x(6x+8)=80 | | -×^2+3×+c=0 | | z2+-5z+4=0 | | 3500=-2580+x | | -6(x+7)=-56 | | 6.5x+12=-24+11x | | -2m+5=4m-13 | | 7=x-3/2 | | 5(2y+5)-25=3(5y+2) | | 6a^2=31a-10 | | -2(3y+3)=9 | | 2/3(2x-5)=9 | | 6(5v-1)=144 | | 7v^2-37v+72=3v^2-v | | 12+9x=12x-6 | | 8x+9+5(x+4)+6=X | | 21k-20=20+19K | | -4t=-96 | | 16+6k=-8k | | 35x+3x-26=3x+5 | | 10u=90 | | 5=2m-13 | | -2+4/7y=3/14+3/7y | | -6(5-8a)=258 | | 2x×2=70 | | F(5)=7x+10 | | 2x=11.23 | | -0.7x(x-7)=0.5x+3.5 |